KASIH SEBAGAI DASAR MEMBANGUN PERSAUDARAAN: Kita Terpanggil untuk Menghadirkan Kasih Sebagai Dasar untuk Membangun Brotherhood di Tengah-tengah Gereja dan Masyarakat - Parsaulian Simorangkir (Majalah Ilmiah METHODA, 2024)
In the midst of this modern era, it feels like people are starting to forget the meaning of Christian brotherhood. The practice of exercising compassion is increasingly fading, especially since people are increasingly busy in their own world. Now, modern humans are more likely to be "indifferent" to other people. They tend to spend their time in cyberspace or social media. Of course, changes in human attitudes greatly influence one another. Jesus' teachings about love no longer concern Christians. To correct this, Christians must look again at what love really means, and what should be done so that brotherhood is not lost further. In this article, the author will discuss how love is the basis for building brotherhood in the context of church and society, with the basis of the Bible from Yohanes 13:34-35